Planning controversies between public administrations. Case study: Madrid capital (Ciudades, 2017)
Conflicts of jurisdiction between public Administrations are especially evident in the framework of the planning processes which refer to capital and major cities. Regional and municipal planning actors show different scales of interest. The case of Madrid capital is one of the best examples of overlapping interests. Madrid as a region, Madrid as a municipal territory, Madrid as the capital of Spain. This article summarizes with some case studies the political tension that arises from the defence of these different goals.
Keywords: regional capitals; urban planning policies; General Land Use Plans; interadministrative conflicts; legal mechanisms of coordination of interests